Melhorias na cementação seletiva de Cd e Ni/Co a partir do eletrólito industrial de zinco - Daísa Carolina Alves Gonçalves (2020)
The selective removal of cadmium, cobalt and nickel from electrolyte prepared on a laboratory scale and industrial zinc sulfate electrolyte (150-160g.L-1) was investigated. The selective removal of cadmium (from 640-740mg.L-1 to < 1mg.L-1) was achieved at ambient temperature, with the staged addition of zinc dust, using a molar zinc/metals ratio of 300%. This molar ratio is 50% lower than those found industrially (e.g., 600-1800%). A cadmium-enriched cement (29% (wt.%) vs. approx. 7% (wt.%) in industrial samples), with a low nickel content (0.05% (wt.%)), considered the most damaging to the cadmium sponge, it was produced in the first stage of purification. The zinc content in cadmium cement was 20% lower when compared to industrial cement. Dendritic formations with a predominance of cadmium were observed in the outer layer of the cementation product, with contents of approximately 60% Cd, 18% Zn, 14% O, and 8% Cu, according to point EDS analyze. In a second stage, the cementation of cobalt and nickel was carried out. The tests were conducted at a temperature of 85ºC, with the addition of activators copper and antimony. The increase in copper concentration (0, 40, 100, 200mg.L-1) in the presence of 10mg.L-1 antimony favored the removal of these impurities. However, problems related to cement redissolution have been identified and the industrial specification has not been met. The pre-activation of the zinc dust in a solution containing 10mg.L-1 Sb and 200mg.L-1 Cu allowed to reach high percentages of cobalt and nickel removal (98.5%), in the first 30min of reaction. In industrial electrolyte, the presence of 150-160g.L-1 Zn did not affect the removal of cobalt, which was equivalent to 97.7% with the use of coarse zinc dust (Znc d50 ≈ 0.14mm) and 98% with the finest zinc dust (Znf d50 ≈ 0.012mm) in just 30min. However, the presence of zinc ions hindered the cementation of nickel for the different granulometry of zinc dust. The maximum percentage of removal was 87%, in 60min, with coarse zinc dust (Znc d50 ≈ 0.14mm). The industrial specification for the purified solution that feeds the zinc electrowinning process was achieved for cobalt (< 0.2mg.L-1) and nickel (< 0.5mg.L-1), after 60min of reaction. Differences in morphology were observed in the zinc dust before and after activation. In the presence of the activators, Cu and Sb, the surface of the zinc dust became rougher and platelet structures were formed. The presence of the well-defined zinc core and the compact, adherent, and external product layer was observed in the cementation products from synthetic and industrial electrolytes. This layer is formed mainly by Zn, O, S and in smaller proportions Cu, Co, Ni, and Sb. Based on the results obtained, a two-stage purification flowsheet was proposed to produce a cadmium-rich cement, with a low nickel content (0.05% (wt.%)) and a cobalt-nickel cement. The process allows the reduction of zinc dust and energy consumption, as well as the reaction time.